2012
DOI: 10.1002/stem.783
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Sustains Long-Term Skeletal Muscle Regeneration by Regulating Fate of Satellite Cells Via Signaling Pathways Requiring Vangl2 and Cyclic GMP

Abstract: Satellite cells are myogenic precursors that proliferate, activate, and differentiate on muscle injury to sustain the regenerative capacity of adult skeletal muscle; in this process, they self-renew through the return to quiescence of the cycling progeny. This mechanism, while efficient in physiological conditions does not prevent exhaustion of satellite cells in pathologies such as muscular dystrophy where numerous rounds of damage occur. Here, we describe a key role of nitric oxide, an important signaling mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
97
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 98 publications
(102 citation statements)
references
References 85 publications
(123 reference statements)
3
97
0
2
Order By: Relevance
“…This is consistent with new evidence supporting the use of NO-donating drugs as therapeutic agents for muscle repair and muscular dystrophy. 8,[30][31][32] It is also consistent with other findings demonstrating that enhancing cGMP signaling improves contractile performance and myocardial metabolic status in the dystrophindeficient heart. 32 It has been shown that NO-donating drugs correct functional ischemia in the setting of muscular dystrophy both in animal models and in humans, by restoring normal blood flow regulation and response to vasoconstrictors.…”
Section: Discussionsupporting
confidence: 89%
“…This is consistent with new evidence supporting the use of NO-donating drugs as therapeutic agents for muscle repair and muscular dystrophy. 8,[30][31][32] It is also consistent with other findings demonstrating that enhancing cGMP signaling improves contractile performance and myocardial metabolic status in the dystrophindeficient heart. 32 It has been shown that NO-donating drugs correct functional ischemia in the setting of muscular dystrophy both in animal models and in humans, by restoring normal blood flow regulation and response to vasoconstrictors.…”
Section: Discussionsupporting
confidence: 89%
“…This also demonstrated better functional gain than L-arginine combined with deflazacort in mdx dystrophic mice (Archer et al, 2006). Another study reported that the NO-releasing drug molsidomine has therapeutic effects in dystrophic mice (Buono et al, 2012). The drug increased muscle fiber regeneration and enhanced muscle function by increasing satellite cell proliferation.…”
Section: A Nitric Oxidementioning
confidence: 99%
“…Hematopoietic stem cell sensitivity to the self-renewal effects of NO may decrease with cell age (99). In vitro, treatment with the NO donor linsidomine (3-morpholinosydnonimine, SIN-1) stimulated proliferation of muscle satellite cells (a precursor muscle cell type), and this was inhibited by concurrent treatment with L-NAME (20). Hematopoietic stem cells treated with an NO donor proliferated faster and had increased expression of the self-renewal transcription factor cMyc (183).…”
Section: A Redox Signaling In Stem Cellsmentioning
confidence: 99%